Efeitos subletais do clorantraniliprole em Bombus morio (Swederus, 1787): análise de órgão-alvo e não alvo - Giroto, Marília Fernandes (Universidade Federal de São Carlos, 2026)
Native bees play an essential role in pollination ecosystem services, yet they are still underrepresented in pesticide risk assessments. In this context, this dissertation aimed to investigate the sublethal effects of chlorantraniliprole through oral exposure in workers of Bombus morio , a species native to Brazil, integrating a literature review and laboratory experiments. The first chapter consisted of a review on the effects of pesticides on Bombus, with emphasis on mortality, behavior, and morphophysiological alterations, as well as a discussion on the limitations of current toxicological protocols. The second chapter involved the adaptation of methodologies for bioassays, including containment and feeding systems, as well as the evaluation of longevity and toxicity at two doses of the insecticide. In the third chapter, sublethal effects were assessed through behavioral and histological analyses of the midgut, Malpighian tubules, and flight muscles. The results demonstrated that B. morio exhibits high tolerance to confinement, with a mean longevity of 30 days, and that chlorantraniliprole did not cause statistically significant mortality at the tested doses. Behavioral analyses did not reveal significant differences among groups. In contrast, histological analyses showed dose-dependent alterations in all three tissues evaluated, including tissue disorganization, loss of cytoplasmic material, and nuclear alterations, suggesting impairment in digestion, absorption, and excretion processes, as well as a possible compromise of muscle function associated with locomotion. Overall, the results indicate that, although not lethal and not inducing detectable behavioral changes in the short term, chlorantraniliprole can cause significant morphophysiological alterations in B. morio, highlighting the importance of considering multiple sublethal endpoints in ecotoxicological assessments and of expanding the inclusion of native species in regulatory testing.
Sublethal effects of chlorantraniliprole on Bombus morio (Swederus, 1787): analysis of target and non-target organs
Keywords: Mamangava; Inseticida; Toxicidade; Efeitos subletais; Alterações histológicas; Bumblebee; Insecticide; Toxicity; Sublethal effects; Histological alterations; CIENCIAS BIOLOGICAS; 2. Fome Zero e Agricultura Sustentável; 15. Vida Terrestre; 13. Ação contra a Mudança Global do Clima; 15. Vida Terrestre